THE ROLE OF FOLLICULAR UNIT GRAFTING IN TREATMENT ALOPECIA - Ayuningtyas, Duhita; Linawati, Made (E-Jurnal Medika Udayana; vol 2 no 8 (2013):e-jurnal medika udayana)
Normal 0 false false false EN-US X-NONE X-NONE Alopecia is usually treatable and self-limited, but it may be permanent. Careful diagnosis of the type of hair loss will aid in selecting effective treatment. Many drugs used to treat alopecia, but in many people not satisfied with the result. One of the treatment currently used to treat alopecia is hair transplantation with follicular unit grafting (FUG). The advantages of hair transplantation is to create a natural appearance, one that mimics natural hair growth both in terms of numbers and pattern /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Alopecia, Hair Transplantation, Follicular Unit Grafting